Web services and enterprise content management Hype vs. reality. - Hough, Charles
New business requirements are leading companies to change the way they deploy enterprise content management (ECM) data and applications. Faced with the limited interoperability and/ or scalability of conventional ECM platforms, developers are turning to Web services as a way to realize ECM functionality and real-time content wherever they are needed within an organization. While this approach is still relatively new and more work remains to be done to improve the effectiveness, it already shows promise as a better way to think about ECM technology.